Sublimation as an Overcoming Mechanism of Anxiety on Bruce Wayne Character in The Dark Knight Trilogy Scripts - Abraham Dauddie Presdyasmara; Pramudana Ihsan; Radius Setiyawan (J-SES : Journal of Science, Education and Studies, 2022)
Abstrak: The research focused on analyzing anxiety and sublimation as a defense mechanism on the main character in The Dark Knight Trilogy scripts. The Psychoanalysis proposed by Sigmund Freud will be used as the main theory, especially the discussion of anxiety and sublimation. The purposes of this research are to depict the sublimation as a defense mechanism that Bruce Wayne used and to analyze how Bruce Wayne overcomes his anxiety through sublimation. This research is qualitative research where the data is taken from scripts The Dark Knight Trilogy, journals, and other resources which are appropriate in conducting the analysis. This study finds that Bruce Wayne’s sublimation defenses are associated with his bad experiences in childhood. The incident of him fell in the old well and the death of his parents lead him to several anxieties, and to cope the anxieties, sublimation is used to overcome his anxieties. From the process of making batarangs and his equipment, acting as a vigilante, and also practicing martial arts, these things can be categorized as Bruce Wayne's sublimation as Batman. Batman is a form of his sublimation mechanism, it is not only the way that he does to cope his anxieties but also a symbol that he created to inspire citizens in Gotham City. Keywords: Anxiet; Defense Mechanis;, Sublimation.